Răspuns :
Răspuns:
[tex]{ \red{d) \: \frac{1}{6} }}[/tex]
Explicație pas cu pas:
[tex]( {}^{ \sqrt{2} )} \frac{1}{ \sqrt{2}} + {}^{ \sqrt{3}) } \frac{1}{ \sqrt{3} } ) \times ( \frac{ \sqrt{2} }{2} - \frac{ \sqrt{3} }{3} ) \\ ( \frac{ \sqrt{2} }{2} + \frac{ \sqrt{3} }{3} ) \times ( \frac{ \sqrt{2} }{2} - \frac{ \sqrt{3} }{3} ) [/tex]
Folosim formula de calcul prescurtat: (a+b)(a-b)=a²-b²
[tex] (\frac{ \sqrt{2} }{2} ) {}^{2} - ( \frac{ \sqrt{3} }{3} ) {}^{2} \\ {}^{9)} \frac{2}{4} - {}^{4)} \frac{3}{9} \\ \frac{18}{36} - \frac{12}{36} = \frac{6}{36} {}^{(6} = { \red{ \frac{1}{6} }} = > varianta \: corecta \: { \red{d)}}[/tex]
Succes!
[tex]\bf \bigg(\dfrac{1}{\sqrt2}+\dfrac{1}{\sqrt3}}\bigg)\cdot\bigg(\dfrac{\sqrt2}{2}-\dfrac{\sqrt3}{3}\bigg)= \bigg(\dfrac{1}{\sqrt2}+\dfrac{1}{\sqrt3}}\bigg)\cdot\bigg(\dfrac{\sqrt2}{\sqrt2\cdot\sqrt2}-\dfrac{\sqrt3}{\sqrt3\cdot\sqrt3}\bigg)=\\ \\ \\ = \bigg(\dfrac{1}{\sqrt2}+\dfrac{1}{\sqrt3}}\bigg)\cdot\bigg(\dfrac{1}{\sqrt2}-\dfrac{1}{\sqrt3}}\bigg)=\bigg(\dfrac{1}{\sqrt2}\bigg)^2-\bigg(\dfrac{1}{\sqrt3}\bigg)^2=\dfrac{^{3)}1}{\ \ 2}-\dfrac{^{2)}1}{\ \ 3}=\dfrac{1}{6}[/tex]